2023
DOI: 10.4236/ajibm.2023.134017
|View full text |Cite
|
Sign up to set email alerts
|

Cashless Payments Impact to Economic Growth: Evidence in G20 Countries and Vietnam—Vietnamese Government with a Policy to Support Cashless Payments

Abstract: This study investigates the relationship between cashless payments and economic growth in G20 countries and Vietnam. Using annual data ranging from 2011 to 2020, the results indicate that cashless payment in the form of check payments stimulates economic growth in G20 countries and Vietnam. Specifically, the growth enhancing effect is found to have an impact on economic growth; Secondly, the positive relationship between economic growth and check payments is robust after controlling for the effect of endogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…India, as a rapidly growing economy, has recognized the potential benefits of embracing a cashless model to bolster economic growth and foster financial inclusion. As the nation strives towards becoming a digital economy, understanding the relationships between key macroeconomic indicators -Gross Domestic Product (GDP), tax collection, interest rates, and the adoption of cashless payment methods -is crucial to formulate effective policies and drive sustainable economic development (Tran et al, 2023;. The adoption of cashless payment methods has been associated with positive impacts on economic growth, where Economy that make the switch to digital tend to experience higher growth rates (Kamlesh, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…India, as a rapidly growing economy, has recognized the potential benefits of embracing a cashless model to bolster economic growth and foster financial inclusion. As the nation strives towards becoming a digital economy, understanding the relationships between key macroeconomic indicators -Gross Domestic Product (GDP), tax collection, interest rates, and the adoption of cashless payment methods -is crucial to formulate effective policies and drive sustainable economic development (Tran et al, 2023;. The adoption of cashless payment methods has been associated with positive impacts on economic growth, where Economy that make the switch to digital tend to experience higher growth rates (Kamlesh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers like Zandi found that cashless payments lead to an upsurge in private consumption, contributing to GDP growth (Zandi et al, 2016). Additionally, studies by Tran have demonstrated a direct link between the growth of e-payments and overall economic expansion (Tran et al, 2023). As India moves forward in its quest to embrace a digital economy, the impact of GDP, tax collection, and interest rates on the cashless ecosystem needs to be carefully analyzed.…”
Section: Introductionmentioning
confidence: 99%